HISTORICAL ASPECT OF LIQUIDAMBAR L. RESEARCH: PERIODIZATION AND PERSPECTIVES - Svitylko, Ігор; Smilyanets, Ніна (Biota. Human. Technology, 2024)
The aims of the stady. Based on the analysis of archival data and scientific publications, to analyze the stages of development of research on representatives of the genus Liquidambar L. in the M.M. Gryshko National Botanical Garden of the National Academy of Sciences of Ukraine (hereinafter – NBG), to find out the promising directions of research on Liquidambar styraciflua L. and L. orientalis Mill. in Ukraine. Methodology. Based on the historical method, we analyzed the development of Liquidambar research in the NBG, presented from the beginning of its foundation (1935) to the present: from 1935 to 2018 – based on the study of the NBG archive materials (about 100 volumes were processed), from 2019 to the present – based on our own research and research of NBG staff based on their publications. All personal data (names, patronymics, positions, departments) about the Botanical Garden employees covered in this publication are presented according to the biographical reference book «They were building a Garden» (Chuvikina & Klymenko, 2009). Scientific novelty. According to the NBG archive, it was found that the first documented mention of Liquidambar styraciflua dates back to 1939 and is preserved in the section «Inventory lists of plants of the scientific plots of the Botanical Garden». In 1959, there was information about the cultivation of another species of this genus, L. orientalis. This is a species of Asian origin, which was obtained from the Sukhumi Botanical Garden. In 2019, a more detailed study of the Liquidambar genus began. In particular, based on the analysis of archival data and scientific publications, the NBG scientists identified four stages of the development of Liquidambar research in the NBS: I – initial (1939–1943). ), which lasted almost from the beginning of the Botanical Garden's foundation and was aimed at collecting planting material (ended unsuccessfully due to World War II); II – the design stage, which lasted from 1944 to 1949, when the Botanical Garden Landscaping Project was drawn up, which included representatives of the genus Liquidambar as part of the North American plant section; III – the stage of growing planting material and passive observation of existing plantings of the Liquidambar genus, where only the number of plants and basic linear indicators (height, trunk and crown diameter) were recorded (1950–2018); IV – aims to comprehensively study the species of the genus Liquidambar in an urban environment and introduce species and cultivars into the landscape compositions of the NBS (from 2019 to the present). Conclusions. A comprehensive study of Liquidambar is being carried out at the M.M. Gryshko National Botanical Garden (NBG): based on the analysis of archival data and scientific publications, NBG scientists have identified four stages of development of Liquidambar research, starting from 1939 to the present. A study of the distribution of Liquidambar and its decorative forms in Ukraine was conducted. It is noted that the use of these trees in urban greening is growing. It is recommended to use representatives of the genus Liquidambar in landscape construction to create groups or as tapeworms in parks, squares, zoos, forest parks, in landscaping of streets, boulevards, squares, adjacent territories, administrative buildings, private estates, in expositions of botanical gardens and arboretums. It is advisable to expand the research on Liquidambar in terms of its invasiveness and medicinal properties as a raw material plant for the pharmaceutical industry. Promising areas of research are further enrichment of the collection fund with new species and forms, study of their ecological, morphological and phenological features, assessment of the prospects for further introduction, search for optimal conditions for use in urban landscaping and park construction, development of recommendations for the reproduction and cultivation of these plants.